2010
DOI: 10.1016/j.pep.2009.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli expression and purification of LL37 fused to a family III carbohydrate-binding module from Clostridium thermocellum

Abstract: The cathelicidin derived human peptide LL37 has a broad spectrum of antimicrobial and immunomodulatory activities. The large variety of biological activities makes LL37 a very promising candidate for clinical applications. The production of biologically active LL37 in large amounts with reduced costs can only be achieved using recombinant techniques. In this work, LL37 has been cloned to the N- and C-termini of a family III carbohydrate-binding module fused to the linker sequence (LK-CBM3) from Clostridium the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 24 publications
(39 reference statements)
0
35
0
Order By: Relevance
“…However, the molecular mechanisms involved in LL37 improvement of healing are not clear. Recently, a recombinant version of this peptide that was able to maintain its antimicrobial activity was produced using a cost-effective method [13]. This recombinant LL37 was shown to accelerate the dexamethasone-induced impaired healing of excisional wounds in C57BL/6 mice [14], further suggesting its potential use as an inexpensive therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecular mechanisms involved in LL37 improvement of healing are not clear. Recently, a recombinant version of this peptide that was able to maintain its antimicrobial activity was produced using a cost-effective method [13]. This recombinant LL37 was shown to accelerate the dexamethasone-induced impaired healing of excisional wounds in C57BL/6 mice [14], further suggesting its potential use as an inexpensive therapeutic agent.…”
Section: Introductionmentioning
confidence: 99%
“…Another application of engineered CBM is to characterize native and engineered carbohydrate biomaterials by using various fluorescent techniques (Gourlay et al 2012;Gao et al 2014). Apart from this, CBMs can serve as attractive affinity tags and, hence, used in the production and purification of antibodies, peptides and enzymes (Hyeon et al 2011(Hyeon et al , 2012Ramos et al 2010;Wan et al 2011). Ramos et al (2013) have reported the production and purification of recombinant antimicrobial peptides in Escherichia coli by using CBM.…”
Section: Applications Of Cellulosomesmentioning
confidence: 99%
“…This scalable method can purify the CBM-tag protein by using a simple unit operation, involving centrifugation or filtration. For example, the cathelicidin-derived human peptide LL37, which has a broad spectrum of antimicrobial and immunomodulatory activities, was cloned to the N-and C-termini of a CBM3 fused to the linker sequence (LK-CBM3) from Clostridium thermocellum (Ramos et al 2010). In the course of processing, the purification was achieved using cellulose CF11 fibers, taking advantage of the CBM3's specific affinity for cellulose.…”
Section: Applications Of Proteins With Fused Cbds Fusion Of One or Momentioning
confidence: 99%